2017
DOI: 10.5114/aoms.2016.58635
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 signaling in patients with chronic heart failure treated with cardiac resynchronization therapy

Abstract: IntroductionIncreased expression of interleukin-6 (IL-6) has been described in left ventricular dysfunction in the course of chronic heart failure. Cardiac resynchronization therapy (CRT) is a unique treatment method that may reverse the course of chronic heart failure (CHF) with reduced ejection fraction (HF-REF). We aimed to evaluate the IL-6 system, including soluble IL-6 receptor (sIL-6R) and soluble glycoprotein 130 (sgp130), in HF-REF patients, with particular emphasis on CRT effects.Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
10
0
3
Order By: Relevance
“…Recent evidence has revealed that inflammation is a critical pathological process of CHF (Dick and Epelman, 2016; Ayoub et al, 2017; Cocco et al, 2017) and high levels of IL-6, a proinflammatory cytokine, have been reported to be an important mediator in chronic inflammatory and cardiovascular disorders (Smart et al, 2006; Bacchiega et al, 2017). Moreover, IL-6 exerts its action through a specific IL-6R and a soluble IL-6 receptor, whereby the IL-6/IL-6R complex binds to the membrane glycoprotein 130 to induce intracellular signaling pathways (Hirota et al, 2004; Ptaszynska-Kopczynska et al, 2017). The JAK-STAT pathway is a characteristic signal transduction pathway that plays a crucial role in this process (Mohri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has revealed that inflammation is a critical pathological process of CHF (Dick and Epelman, 2016; Ayoub et al, 2017; Cocco et al, 2017) and high levels of IL-6, a proinflammatory cytokine, have been reported to be an important mediator in chronic inflammatory and cardiovascular disorders (Smart et al, 2006; Bacchiega et al, 2017). Moreover, IL-6 exerts its action through a specific IL-6R and a soluble IL-6 receptor, whereby the IL-6/IL-6R complex binds to the membrane glycoprotein 130 to induce intracellular signaling pathways (Hirota et al, 2004; Ptaszynska-Kopczynska et al, 2017). The JAK-STAT pathway is a characteristic signal transduction pathway that plays a crucial role in this process (Mohri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Modified Duke lead criteria p = 0.003 relatively low specificity, and thus some new, cardiac specific markers might be more useful [16,17]. Nevertheless, our observations indicate that CDRIE should be suspected in every CRT patient who did not respond well to antibiotic therapy, has recurrent fever or has increased markers of infection.…”
Section: 5%mentioning
confidence: 94%
“…Повышенная экспрессия IL-6 в миокарде наблюдается на конечной стадии ХСН как ишемической, так и не ишемической этиологии. Интересно и то, что сигнальная передача gp130, связанная с IL-6, может быть кардиозащитной, тогда как чрезмерная активация gp130 приводит к прогрессированию ХСН [27].…”
Section: адаптивный иммунный ответunclassified